7x+6=-5x

Simple and best practice solution for 7x+6=-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+6=-5x equation:


Simplifying
7x + 6 = -5x

Reorder the terms:
6 + 7x = -5x

Solving
6 + 7x = -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
6 + 7x + 5x = -5x + 5x

Combine like terms: 7x + 5x = 12x
6 + 12x = -5x + 5x

Combine like terms: -5x + 5x = 0
6 + 12x = 0

Add '-6' to each side of the equation.
6 + -6 + 12x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 12x = 0 + -6
12x = 0 + -6

Combine like terms: 0 + -6 = -6
12x = -6

Divide each side by '12'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 5x+7(x+1)+3=10-6x | | x-.2x=1300 | | 0.16(5x-2)=0.4x+17 | | 122-2x=16x+20 | | w^5x^4y^5-wxy=0 | | 77.50=.15x+10 | | -12a^6+8a^3=0 | | 18x^3-60x^2=-50x | | 12x*x^2=0 | | 6x-8=82 | | 3x+21=63 | | 187-5x=40x+22 | | 16x^2-24x+9=13 | | 12x*1x^2=0 | | 12x*1x^2=x | | 2x*1x^2=0 | | 2x*1x^2=x | | 3x^2+5x-18=0 | | 99-3x=4x | | 10x^2+31x-14=0 | | 4m^2+3m=1 | | b+2.35=9.78+2b+7.22 | | v^2-9v-10=0 | | 4a-12b+20a= | | m^2+9m+18=0 | | 4h^2-4h+1=0 | | e^2-5e-84=0 | | 2(3-7y)=4y+2 | | 6l^2-5l-4=0 | | 3x+9+4x+4=8x+5 | | o^2+24o+144=0 | | 3x+9+4x+4=8x |

Equations solver categories